Herrera Ortega, Silvia. La canción política en Sergio Ortega. Santiago De Chile: Ril Editores, 2023, 390 pp. ISBN: 978-956-01-1501-0 - Soto Logos, Ximena (2024)
Fil: Soto Logos, Ximena. Universidad de Valparaíso; Chile